Trends in Leadership at Pediatric Orthopaedic Fellowships. Issue 6 (20th July 2021) - Cohen, Lara L.; Sama, Andrew J.; Schiller, Nicholas C.; Spielman, Amanda F.; Donnally, Chester J.; Shore, Benjamin J.; Glotzbecker, Michael P.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Pediatric orthopaedic fellowship directors (FDs) have a valuable impact on the education of trainees and future leaders in the field. There is currently no research on the characteristics of pediatric orthopaedic FDs. Methods: Programs were identified using the Pediatric Orthopaedic Society of North America fellowship directory. Operative, nonoperative, and specialty programs were included. Data was collected through Qualtrics survey, e-mail, telephone, and online searches. Variables included demographics (age, sex, race/ethnicity), Hirsch index (h-index) as a measure of research productivity, graduate education, residency and fellowship training, years of hire at current institution and as FD, and leadership roles. Results: Fifty-five FDs were identified. The majority (49/55, 89%) were male and 77% (27/35) were Caucasian. The mean age at survey was 51.1±8.2 years. The mean h-index was 17.2. Older age correlated with higher h-index ( r =0.48, P =0.0002). The average duration from fellowship graduation to FD appointment was 9.6±6.7 and 6.9±6.1 years from institutional hire. Sixteen FDs (29%) had additional graduate level degrees. Almost all (52/55, 95%) FDs completed orthopaedic surgery residencies and all graduated fellowship training. Twenty-nine percent (16/55) completed more than 1 fellowship. Most FDs (51/55, 93%) completed a fellowship in pediatric orthopaedic surgery. Ten FDs (18%) completed pediatric orthopaedic surgery fellowships that included spine-specific training. One-third of all current FDs were fellowship-trained at either Boston Children's Hospital (9/55, 16%) or Texas Scottish Rite Hospital for Children (9/55, 16%). Conclusions: Pediatric orthopaedic FDs are typically early-career to mid-career when appointed, with a strong research background. Nearly a third completed additional graduate degrees or multiple fellowships. Although male dominated, there are more female FDs leading pediatric orthopaedic programs compared with adult reconstruction, trauma, and spine fellowships. As fellowships continue to grow and diversify, this research will provide a baseline to determine changes in FD leadership.